Asia as an Attractive Localization for Foreign Direct Investments of the European Union Member States - Stawicka, Magdalena Kinga (Azja jako atrakcyjne miejsce do lokowania bezpośrednich inwestycji zagranicznych dla krajów Unii Europejskiej, 2010)
To the end of 2008 Asian states have attracted capital in form of foreign direct investments amounting to 2.5 trillion USD. Just in 2008 investors located nearly 400 billion USD in these economies. Main beneficiaries of the foreign direct investments are: Hong Kong, China, India, Saudi Arabia, Japan and Singapore. It is estimated that the European Union economies annually increase in value of investments in Asian states and presently their share in shape of the global value of FDI inflow amounts to approximately 15% and it grows up annually. Competitors for Asian states offering better and better conditions are Middle-East states which are still characterized by low production costs and, first of all, by localization close to European Union's states, which makes up a hazard for increase in inflow of the foreign direct investments' inflow to Asia.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 103-111
Keywords: Asia; Europe; FDI; investments; capital flow